Seismic behavior of composite interior joints of prefabricated H-shaped steel reinforced concrete column - steel beam. (February 2020) - Wu, Chenglong; Liu, Jiming; Tan, Wenya; Wang, Pengfei
Abstract: To better meet the requirements of building industrialization, this study proposes a Modular Prefabricated Composite Interior Joint (MPCIJ), which consists of node modules, prefabricated H-shaped steel–concrete columns, and steel beams. The failure process and characteristics of three MPCIJ joints under low cyclic reciprocating loading are analyzed. Seismic behaviors such as skeleton curve, hysteresis curve, ductility deformation, energy dissipation, strength, and stiffness degradation of MPCIJ are studied. The variable parameters of three MPCIJ specimens are the stiffness ratios (beam to column). The test results show that with increasing beam to column stiffness ratio, MPCIJ specimens gradually develop from clear beam end bending failure to joint shear failure and column end compression-bending failure. Each node has experienced the elastic stage, the elastic–plastic stage, and the failure stage. Load-displacement curves of MPCIJ specimens are relatively full, showing high bearing capacity and strong energy consumption. The average equivalent viscous damping coefficient ranges between 0.30 and 0.37, and the average ductility coefficient ranges between 3.60 and 4.25, which meets the seismic performance requirements. The beam to column stiffness ratio exerts less influence on the strength degradation coefficient and stiffness degradation coefficient of MPCIJ specimens, and their performance degradation ability remains relatively stable. In summary, the MPCIJ specimen offers high bearing capacity and good seismic performance. At the same time, the influence of the internal welding quality of the joint module cannot be ignored, and the weld strength should be strictly guaranteed during processing.